2019
DOI: 10.1186/s13028-018-0438-9
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathological findings suggestive for a stroke in an alpaca (Vicugna pacos)

Abstract: BackgroundThis case report describes a focal brain lesion in an alpaca (Vicugna pacos). Although this is a restricted study based on a single animal, neuropathological features are reported that are most likely attributed to a vascular event with either ischemic or hemorrhagic pathology. Concerning translational issues, these findings extend neurovascular unit concept to the alpacas’ brain and qualify a larger panel of stroke tissue markers for further exploration of ischemic or hemorrhagic consequences beyond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 30 publications
4
13
0
Order By: Relevance
“…Our study showed low proportions of E. coli resistance to tetracycline (16.83%) in comparison to fecal E. coli resistance to tetracycline as reported in the NARMS, 2016 report and other dairy studies of AMR in fecal commensal bacteria (Cummings, Aprea & Altier, 2014;Boireau et al, 2018;Aasmäe et al, 2019). Such a difference could be due to spatiotemporal changes between the studies, specifically due to implementation of SB 27 in CA prior to initiation of the current study.…”
Section: Discussion Amr In E Coli Isolatessupporting
confidence: 45%
See 1 more Smart Citation
“…Our study showed low proportions of E. coli resistance to tetracycline (16.83%) in comparison to fecal E. coli resistance to tetracycline as reported in the NARMS, 2016 report and other dairy studies of AMR in fecal commensal bacteria (Cummings, Aprea & Altier, 2014;Boireau et al, 2018;Aasmäe et al, 2019). Such a difference could be due to spatiotemporal changes between the studies, specifically due to implementation of SB 27 in CA prior to initiation of the current study.…”
Section: Discussion Amr In E Coli Isolatessupporting
confidence: 45%
“…In the NAHMS Dairy 2014 study (USDA, 2018), cephalosporins were used as the primary antimicrobials to treat mastitis on 63.2% of operations; first-generation cephalosporins were used by 29.8% of operations and third generation cephalosporins by 33.4%. Low levels of E. coli resistance (<5%) to ceftiofur, aminoglycosides, trimethoprim-sulfamethoxazole, and fluoroquinolones were reported in previous studies on fecal samples of dairy cows (Carson et al, 2008;Boireau et al, 2018;Aasmäe et al, 2019) and feedlot cattle Gow et al, 2008;Benedict et al, 2013;Waldner et al, 2019).…”
Section: Discussion Amr In E Coli Isolatesmentioning
confidence: 66%
“…Therefore, the determination of the efficacy of teat disinfectant products against bacteria naturally present on the teat skin is important. A study determined the impact of ten pre- and post-milking teat disinfectant products with different ingredients of varying concentrations on the reduction of teat skin bacterial load without damaging the teats [ 29 ]. The results revealed that all the tested teat disinfectant products reduced the teat bacterial load for all three bacterial groups [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results revealed that all the tested teat disinfectant products reduced the teat bacterial load for all three bacterial groups [ 26 ]. Of these, it was notable that the product containing 0.6% w/w diamine was the most effective against the bacterial populations of staphylococcal and streptococcal isolates on teat skin with a reduction of 90% and 94%, respectively, while another product containing 0.5% w/w iodine resulted in the highest reduction (91%) in coliforms on teat skin [ 29 ]. The results from this study suggest that specific bacterial population loads on teats can be reduced using different teat disinfectant formulations.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies on the on-farm use of alternative medicines highlight farmers' “incorrect” use of these medicines. With respect to homeopathy, in particular, farmers are said not to perform a sufficiently thorough diagnosis of the animal's state of health, and to have a tendency to simplify the homeopathic approach by linking a given remedy with a given illness ( 38 , 39 ). The “unicist” homeopathic approach—the prevailing approach in the world of veterinary practice—holds that every sick individual is affected in a unique way by a given disease, and thus requires a specific, unique treatment.…”
Section: Discussionmentioning
confidence: 99%